Developing the Islamic Reading Center Through Fostering the Village Youth Organization to Improve Children’s Literacy - Wardhani, Irma Yuniar; Fakhri Auliya, Nanang Nabhar; Fuadah, Laily (PALASTREN: Jurnal Studi Gender, 2021)
The study of literacy always becomes the main issue in education, because this skill is a benchmark for the progress and development of a nation. Indonesia is a large country with a large area, however with its wide area it turns out to be an obstacle in terms of equalizing education in Indonesia. In fact, some rural villages have not had adequate access to education and it causes the paradigm about education among rural villages is less open.  Moreover, Indonesia is a country which majority of the population are Muslims, so the literacy skills improvement program which is being pursued should have an Islamic value. . Unfortunately, there have not been many reviews about increasing literacy skills based on Islamic education. Therefore, it needs an effort that can develop literacy skills for children especially for the nation's next generation. The fostering of villages youth organizations through the Islamic Reading Center (IRC) which aims to increase children's literacy is a literacy collaborative (LC) program starting from rural villages’ level, local government and central government which involves youth organization from the rural villages’ level, sub-district, regency, education and culture agency, social agency, regional and national libraries, and the directorate general of Islamic education of religious ministry of Republic of Indonesia. The Islamic reading center provides Islamic books and media that can be managed by the youth organizations in a rural village. So, through Islamic reading centers and literacy activities, it can increase literacy skills in rural villages which need more attention in education.